Caption in Mandarin: Necessity or Existence? - Ventivani, A (KnE Social Sciences, 2019)
The purpose of this research is to find out the reasons of the student of Mandarin department using Mandarin Language in social media, forms, and responses from Mandarin native to see this phenomenon. This research use qualitative descriptive approach. The data source of this research is observation sheet, questionnaire sheet and interview result. The data that obtained from the field were analyzed using Miles and Huberman analysis by researcher as a main instrument. Results of this study indicate that student of Mandarin department using Mandarin Language in social media (caption and status in social Media) is code mixing. Thos is show by the reason students use Mandarin Language on social media only as an existence without any particular reason in one situation. Beside that, response of Mandarin Native are divided into two views, namely as an educator and as a common Chinese people. As an educator, Mandarin native finds it helpful to know the students’ Mandarin abilities, especially Mandarin language skill. As a common Chinese people, Mandarin native feels proud because foreigners can use Mandarin Language. Keywords: Social Media, Mandarin Language, Mixing code